Optical Coherence Tomography to Evaluate Plaque Burden and Morphology in Patients With Takotsubo Syndrome - Ingo Eitel; Thomas Stiermaier; Tobias Graf; Christian Möller; Karl‐Philipp Rommel; Charlotte Eitel; Gerhard Schuler; Holger Thiele; Steffen Desch (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Disrupted atherosclerotic plaques in the left anterior descending coronary artery are discussed controversially as a potential pathophysiological mechanism in Takotsubo syndrome (TTS). Therefore, the aim of the present study was to assess plaque burden and morphology by using optical coherence tomography in patients with TTS. Methods and Results A total of 23 consecutive TTS patients were included in this single‐center study and underwent optical coherence tomography imaging of the left main coronary artery and the left anterior descending coronary artery at acute presentation. All patients fulfilled the established diagnostic criteria for TTS and the diagnosis was confirmed with a multimodality imaging approach including cardiac magnetic resonance in 16 patients (69.6%). Atherosclerotic plaques located in the left anterior descending coronary artery or both the left anterior descending coronary artery and the left main coronary artery were detected in 16 TTS patients (69.6%), with 6 patients exhibiting multiple plaque types. In addition to the predominant fibrocalcific (52.2%) and lipid‐rich plaques (30.4%), thin‐cap fibroatheromas were also found in 6 patients (26.1%). However, ruptured plaques or intracoronary thrombi were not observed. Vessel stenosis >50% was found in 3 patients (13.0%) by analyzing cross‐sectional areas. Clinical characteristics and cardiac magnetic resonance findings did not differ significantly between TTS patients with and without atherosclerotic plaques. Conclusions Using optical coherence tomography, the present study revealed a high prevalence of atherosclerotic plaques in patients with TTS, including a considerable number of highly vulnerable thin‐cap fibroatheromas. However, ruptured plaques or intracoronary thrombi were not observed and are therefore most likely not the underlying mechanism of TTS.